Optimalisasi Manajemen Keuangan di MA Darul Ulum Muhammadiyah Galur - Arif Mujahidin; Farid Setiawan; Hanifah Dwi Astiyani; Anisa Listiyani; Latsa Alyautami (Yayasan Literasi Sains Indonesia, 2022)
This study aims to identify and understand financial management in the MA Darul ulum Muhammadiyah Galur school. The method used in this research is a qualitative approach by means of interviews and observations. The research subject is the School Treasurer. The results of this study indicate the existence of school financial management in fulfilling the educational facilities and infrastructure of MA Darul Ulum Muhammadiyah Galur which aims to determine various kinds of school internal policies that affect the quality and performance of schools. From this research, it shows that MA Darul Ulum Muhammadiyah Galur has managed school finances well which can be seen in the facts that have been found in the field showing that financial management at MA Darul Ulum Muhammadiyah Galur has been effective, efficient and transparent.